Penggunaan Media Pembelajaran Wordwall Terhadap Hasil Belajar Bahasa Inggris Siswa Sekolah Dasar - Adilah Fauziyah; Yani Fitriyani; Nanan Abdul Manan; Oman Hadiana; Sainab Mong-alee (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2023)
The low learning outcomes of class 1 Prathom Anuban Wangmai Sasanasart School in English material is one of the problems that occurs, this is due to the absence of the use of media in learning. This study aims to describe the application of Wordwall media in improving student learning outcomes in English lessons. This study type is quantitative research with a Pre-Experimental Design approach (Non-design), with a One Group Pretest-Posttest Design. The subjects were the first-grade class of Anuban Wangmai Sasanasart School, Tha Phae District, Satun Province, Thailand. The data acquisition techniques were obtained through a multiple choice test or pretest and posttest. The data analysis used by researchers was in the form of instruments and statistical tests. The research results obtained are (1) learning outcomes after using Wordwall media differ from the learning outcome before using Wordwall media. (2) there is an increase in learning outcomes after using Wordwall media compared to the learning outcome before the implementation. This study concludes that the application of Wordwall media has an impact on improving student learning outcomes. This research recommends that the Anuban Wangmai Sasanasart School teachers probably use Wordwall media in learning English.